Managing The Risk of Nutritional Deficiencies Through Nutritional Management (Structured Dietary Education) in Children with Dengue Fever in Hospital - Haryani, Siti; Surya Adi Pratama, Misbakhul (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Dengue hemorrhagic fever remains a major public health issue, particularly among children, as the number of people affected by this disease is quite high and the risk of complications is also significant. Children with dengue hemorrhagic fever often experience symptoms such as loss of appetite, nausea, and vomiting, which cause them to lose their appetite. In addition, their bodies require more energy to fight the infection, putting them at risk of nutritional deficiency. This study aims to explain how to manage the risk of nutritional deficiency by providing education on planned dietary patterns for children suffering from DBD. The method used is a descriptive case study approach focusing on the nursing care process, which includes data collection, problem identification, problem management, implementation of interventions, and outcome assessment. The primary nursing diagnosis identified was the risk of malnutrition due to decreased appetite and inadequate food intake. Interventions focused on managing nutrition and educating families about dietary patterns, such as feeding small but frequent meals, choosing easily digestible foods with high nutritional value, and ensuring fluid needs are met. The program was implemented by monitoring the types and amounts of food consumed, checking body weight, and providing guidance to parents on healthy and appropriate eating habits during illness and recovery. The results showed an increase in nutrient intake, greater consumption of healthy foods, and improved family knowledge regarding children’s nutritional needs. Education on regular eating habits has been shown to help prevent nutritional problems and support the recovery of children with dengue fever.